Usulan Peningkatan Kualitas Imprabox Menggunakan Pendekatan Lean Six Sigma dengan Simulasi Monte Carlo (Studi Kasus: Perusahaan Packaging) - Felix Yohannes Panjaitan; Winarno Winarno; Fahriza Nurul Azizah (Engineering Faculty at Universitas Singaperbangsa Karawang, 2022)
The tight competition in the industry at this time makes every company must improve the quality of each product. To optimize the production process, waste becomes the main inhibiting factor that can reduce the company's image. PT Jaya Prakarsa is a packaging company which is currently facing the problem of the emergence of waste in each of its production processes for the final product which is called Imprabox. This study aims to reduce waste in the Imprabox production process using the lean six sigma method with the Define, Measure, Analyze, Improve & Control (DMAIC) stages and Monte Carlo simulation. The results of the define stage show that the defect waste becomes critical waste with a value of 42.3%. At the measure stage, the results from the p control chart show that the existing quality is still not fully controlled. The sigma level for the average process from February to March 2022 is 2.63 and the Process capability index (Cpk) value is 0.1532. This Cpk value is still less than 1.31, indicates that the company lacks production process capability. The cause and effect of the emergence of defects are then analyzed using a fishbone diagram at the analyze stage which will be repaired using 5W + 1H at the improve stage. Based on the results of the MC simulation with three successful scenarios of quality improvement of 50%, 75% and 100%, it shows that there is an increase in the processing capability for the company by 403.9%, 425.5%, and 426.9%, respectively.